The Effect Of Work Motivation And Work Discipline On Employee Performance Of Pt Pos Indonesia (Persero) South Tangerang Branch Office - Julius, Mario; Flower, Astra Gracia (Transforma Jurnal Manajemen, 2024)
The purpose of this study was to determine the effect of work motivation and work discipline on employee performance at PT Pos Indonesia (Persero) South Tangerang Branch Office. The method used is an associative method with a quantitative approach with a population of 140 people. The sampling method uses a random sample with the Slovin formula which uses a tolerance limit of 10% or 0.1, so that the number of samples becomes 58 respondents. Data processing methods include classical assumption tests, simple and multiple linear regression tests, simple and multiple correlation coefficient tests, simple and multiple determination coefficient tests, and t and f hypothesis tests. The results of the simple determinant coefficient test of work motivation have a contribution of 0.560 or 56% to employee performance, the simple determinant coefficient test of work discipline has a contribution of 0.359 or 35.9% to employee performance, while the multiple determination coefficient test of work motivation and work discipline has a contribution of 0.582 or 58.2% to employee performance. Based on the t hypothesis test, it shows that work motivation has an effect on employee performance because the calculated t value> t table or 8.445> 1.673 and the sig value is 0.000 <0.1 and work discipline has an effect on employee performance because the calculated t value> t table or 5.606> 1.673 and the sig value is 0.002 <0.1. And simultaneously work motivation and work discipline have an effect on employee performance, this is evidenced by the calculated f value> f table or 40.721> 2.40 and the sig value is 0.000 <0.05.